Large Eddy Simulation of a Turbulent Spray Jet Flame Using Filtered Tabulated Chemistry. (19th March 2020) - Chatelier, Adrien; Fiorina, Benoît; Moureau, Vincent; Bertier, Nicolas
Abstract : This work presents Large Eddy Simulations of the unconfined CORIA Rouen Spray Burner, fed with liquid n -heptane and air. Turbulent combustion modeling is based on the Filtered TAbulated Chemistry model for LES (F-TACLES) formalism, designed to capture the propagation speed of turbulent stratified flames. Initially dedicated to gaseous combustion, the filtered flamelet model is challenged for the first time in a turbulent spray flame configuration. Two meshes are employed. The finest grid, where both flame thickness and wrinkling are resolved, aims to challenge the chemistry tabulation procedure. At the opposite the coarse mesh does not allow full resolution of the flame thickness and exhibits significant unresolved contributions of subgrid scale flame wrinkling. Both LES solutions are extensively compared against experimental data. For both nonreacting and reacting conditions, the flow and spray aerodynamical properties are well captured by the two simulations. More interesting, the LES predicts accurately the flame lift-off height for both fine and coarse grid conditions. It confirms that the modeling methodology is able to capture the filtered turbulent flame propagation speed in a two-phase flow environment and within grid conditions representative of practical applications. Differences, observed for the droplet temperature, seem related to the evaporation model assumptions.